Setting an International Research Agenda for Fear of Cancer Recurrence: An Online Delphi Consensus Study - Shaw, Joanne; Kamphuis, Helen; Sharpe, Louise; Lebel, Sophie; Smith, Allan Ben; Hulbert-Williams, Nicholas; Dhillon, Haryana Mary; Butow, Phyllis (Frontiers in Psychology, 2021)
Background: Fear of cancer recurrence (FCR) is common amongst cancer survivors. There is rapidly growing research interest in FCR but a need to prioritise research to address the most pressing clinical issues and reduce duplication and fragmentation of effort. This study aimed to establish international consensus among clinical and academic FCR experts regarding priorities for FCR research. Methods: Members of the International Psycho-oncology Society (IPOS) Fear of Cancer Recurrence Special Interest Group (FORwards) were invited to participate in an online Delphi study. Research topics identified in Round 1 were presented and discussed at a focus group (Round 2) to consolidate the topics prior to presentation in further survey rounds (Round 3) aimed at gaining consensus on research priorities of international significance. Results: Thirty four research topics were identified in Round 1 and these themes were consolidated into 6 overarching themes through a focus group discussion with FCR experts. The 34 research topics were presented in subsequent rounds of the delphi technique. Consensus was reached for 27 items in round 3.1. A further 4 research topics were identified by panellists and included in round 3.2. After round 3.2, 37 individual research topics were ratified by the panellists. Given the high levels of consensus and stability between rounds no further rounds were conducted. Overall intervention research was considered the most important focus for FCR research. Panellists identified models of care that facilitate greater access to FCR treatment and evaluation of the effectiveness of FCR interventions in real world settings as the two research topics of highest priority. Defining the mechanisms of action and active components across FCR/P interventions, was the third highest priority identified. Conclusions: The findings of this study outline a research agenda for international FCR research. Intervention research to identify models of care that increase access to treatment, are based on a stepped care approach and can be delivered within routine clinical care, were identified as research areas to prioritise. Greater understanding of the active components and mechanisms of action of existing FCR interventions will facilitate increased tailoring of interventions to meet patient need.